Gender in the making: An empirical approach to understand gender relations in the maker movement. Issue 145 (January 2021) - Eckhardt, Jennifer; Kaletka, Christoph; Pelka, Bastian; Unterfrauner, Elisabeth; Voigt, Christian; Zirngiebl, Marthe
Highlights: Between 55% and 70% of makers are male. Maker spaces put much effort in attracting a diverse clientele by offering free trainings to all, having no or low membership fees or by reducing the complexity of machines through practical and simple procedures. Quantitative data regarding use times by gender reflect these findings relating to gendered objects. A division between 'crafting' and 'making' becomes visible between female and male makers: While men tend to have an engineering background, female makers often work in design, communication and social relations area. Our study reveals a lack of female role models as maker space managers. Abstract: In this paper we explore gender issues in the maker movement using four different methods of data analysis: standardised questionnaires, analysis of makerspaces' social media, statistical analysis of machine use and the coding of interviews and focus groups. The objective is to give a voice to female makers and makerspace managers, looking at the maker movement from an inside perspective. The paper demonstrates how gendered stereotypes are still reproduced within the maker movement. Makerspaces still attract considerably more males than females and exhibit a primarily "male" culture, reflected in the interior design of places, or by the language and attitudes of their members. Females in makerspaces, however, often have a background in communications, arts or design, as opposed to the coding or engineering background of the males. Previous research has shown how machines and materials also take on gendered connotations. The "genderisation" of objects refers to an attributed gender-specific use of machines. An example here could be that 3D printing, which is more often used by female makers compared to male members of makerspaces. Our research also identifies promising approaches for tackling the issue of gender imbalance. The maker movement has significant potential to improve gender equality as younger generations bring societal change to makerspaces and break with stereotypes. One of the findings our paper puts forward is the lack of female role models, especially in leading positions. Our data suggest that the maker scene still has to develop a tradition in reflecting questions around gender stereotypes or their role in partly reproducing them. Hence, we argue that the maker community should be more attentive to this issue and should make a concerted effort to become more diverse. Overall, our case research did not reveal any explicit animosity to gender questions; on the contrary, male makers and most maker communities showed great interest in avoiding gender stereotyping. We suggest applying the Bechdel-Test as a simple tool for clarifying gender topics and encouraging self-reflection among makers. Overall, our paper aims to support makerspaces that want to make diversity part of their strategy for future growth.